2008
DOI: 10.1038/cdd.2008.96
|View full text |Cite
|
Sign up to set email alerts
|

On the role of major vault protein in the resistance of senescent human diploid fibroblasts to apoptosis

Abstract: Major vault protein (MVP), the main component of vault complex, is overexpressed in many multidrug-resistant cancer cell lines, suggesting a possible role for MVP in cell signaling and survival. In this study, we have found that MVP is markedly increased in senescent human diploid fibroblasts (HDFs) as well as in aged organs. We examined whether MVP expression might be affected by apoptotic stress in an aging-dependent manner. We treated young and senescent HDFs with apoptosis-inducing agents such as H 2 O 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…On the other hand, Dortet et al have suggested that MVP may, by interacting with the bacterial protein InlK, facilitate the evasion of opportunistic bacterium by impairing the formation of autophagous vesicles (32). Similarly, we demonstrate here that a SR-A-MVP-caveolin complex serves as a prerequisite for apoptosis in macrophages whereas Ryu et al have reported that MVP affords senescent fibroblast cells the resistance to oxidative stress induced apoptosis (23). The two seemingly distinct aspects of MVP activity are probably indications of its flexibility in mediating cellular events.…”
Section: Discussionsupporting
confidence: 34%
See 1 more Smart Citation
“…On the other hand, Dortet et al have suggested that MVP may, by interacting with the bacterial protein InlK, facilitate the evasion of opportunistic bacterium by impairing the formation of autophagous vesicles (32). Similarly, we demonstrate here that a SR-A-MVP-caveolin complex serves as a prerequisite for apoptosis in macrophages whereas Ryu et al have reported that MVP affords senescent fibroblast cells the resistance to oxidative stress induced apoptosis (23). The two seemingly distinct aspects of MVP activity are probably indications of its flexibility in mediating cellular events.…”
Section: Discussionsupporting
confidence: 34%
“…MVP expression and/or activity is known to fluctuate according to environmental signals, essentially positioning MVP as a stress protein (21)(22)(23)(24). It has been proposed to carry out important pathobiologi- cal functions in drug resistance, intracellular transport, cellular differentiation, innate immunity, virus infections, and cell survival (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Among the Bag3 novel interactors, we identified MVP and associated proteins, which form a protein complex that is strongly associated with chemotherapy resistance. MVP has been recently described as associated with resistance to apoptosis in senescent fibroblasts (33). We demonstrated that MVP gene-silencing switches the response from senescence to apoptosis.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast to dividing cells, senescent cells display characteristic phenotypic alterations such as an increase in the expression of cell cycle inhibitory molecules (Demidenko and Blagosklonny, 2008), a large and flat morphology (Cho et al, 2004), higher senescence-associated β-galactosidase activity (SA-β-gal) (Dimri et al, 1995;Kang et al, 2009), accumulation of oxidative damage (Harman, 1956), hypo-responsiveness to growth factors (Kim et al, 2010) and apoptotic resistance (Ryu et al, 2008). In various cellular processes, morphological changes play an important role in cellular function.…”
Section: Introductionmentioning
confidence: 99%